Ankle Distraction Arthroplasty: Indications, Technique, and Outcomes. Issue 2 (February 2017) - Bernstein, Mitchell; Reidler, Jay; Fragomen, Austin; Rozbruch, S. Robert
Abstract : Ankle distraction is an alternative to ankle arthrodesis or total ankle arthroplasty in younger patients with arthritis. Ankle distraction involves the use of external fixation to mechanically unload the ankle joint, which allows for stable, congruent range of motion in the setting of decreased mechanical loading, potentially promoting cartilage repair. Adjunct surgical procedures are frequently done to address lower-extremity malalignment, ankle equinus contractures, and impinging tibiotalar osteophytes. Patients can bear full weight during the treatment course. The distraction frame frequently uses a hinge, and patients are encouraged to do daily range-of-motion exercises. Although the initial goal of the procedure is to delay arthrodesis, many patients achieve lasting clinical benefits, obviating the need for total ankle arthroplasty or fusion. Complications associated with external fixation are common, and patients should be counseled that clinical improvements occur slowly and often are not achieved until at least 1 year after frame removal.